2014
DOI: 10.1590/0102-311x00084013
|View full text |Cite
|
Sign up to set email alerts
|

Perfil e situação de insegurança alimentar dos usuários dos Restaurantes Populares no Brasil

Abstract: O objetivo foi identificar o perfil dos usuários do programa Restaurantes Populares e suas associações com a situação de insegurança alimentar domiciliar. Trata-se de estudo transversal com amostra aleatória de 1.637 usuários. Foi utilizado um questionário com variáveis socioeconômicas, a Escala Brasileira de Insegurança Alimentar e aferidos peso e altura. Foram aplicados o teste de qui- quadrado, cálculo das razões de prevalência (RP) bruta e ajustada, utilizando-se o modelo de regressão de Poisson. Foram pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
36
1
24

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(61 citation statements)
references
References 32 publications
(28 reference statements)
0
36
1
24
Order By: Relevance
“…Some studies have already identified a relation between food insecurity and overweight, since it has increased in the economically disadvantaged classes, probably due to the acquisition of foods with low nutritional value and high caloric density at lower prices 9,25,26 . In contrast to other studies 9,[27][28][29][30] , schooling showed no association with FNI, probably because this population is very homogeneous regarding low schooling, a result also found in other settled populations 7,21,31 . Low schooling contributes to people generally not getting well paid work opportunities outside the settlements, not promoting increased income and decreased food insecurity.…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…Some studies have already identified a relation between food insecurity and overweight, since it has increased in the economically disadvantaged classes, probably due to the acquisition of foods with low nutritional value and high caloric density at lower prices 9,25,26 . In contrast to other studies 9,[27][28][29][30] , schooling showed no association with FNI, probably because this population is very homogeneous regarding low schooling, a result also found in other settled populations 7,21,31 . Low schooling contributes to people generally not getting well paid work opportunities outside the settlements, not promoting increased income and decreased food insecurity.…”
Section: Discussioncontrasting
confidence: 99%
“…It is known that low family income is one of the main determinants of FNI. 9,[27][28][29][30]32,33 In this population, the average monthly income was R$ 651.00 (US$192,69) , a figure slightly lower than the minimum wage in force in 2013, which was R$ 678.00 (US$ 200,59). Some 83.2% of the families received some type of government CTP.…”
Section: Discussionmentioning
confidence: 99%
“…Esse resultado difere do encontrado em estudo com famílias dos municípios do norte de Alagoas 19 e entre trabalhadores de restaurantes populares do Rio de Janeiro 26 ; contudo se assemelha ao achado entre beneficiários do Bolsa Família em Toledo (Paraná) 27 , famílias com adolescentes na Amazônia Legal Brasileira 28 , usuários de restaurantes populares no Brasil 29 e famílias residentes em uma área de abrangência do Núcleo de Apoio à Saúde da Família em Itumbiara (Goiás) 23 . Como neste trabalho, foi utilizado o nível econômico do domicílio, o qual considera a escolaridade do chefe da família para a sua construção.…”
Section: Discussionunclassified
“…Regarding successful food security policies, Brazil has been known worldwide for reducing food insecurity by improving food access, income generation, supporting the food production by small farmers, and enhancing food security governance including civil society organizations 9,10,11 . Most importantly, alongside these developments, Brazil built a robust legal and institutional framework for food security, transforming the fight against hunger into a state obligation 6,12,13,14 .…”
Section: Introductionmentioning
confidence: 99%